2014
DOI: 10.1007/s12275-014-3658-3
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Bacterial microRNAs and possible targets in human cell transcriptome

Abstract: Recent studies have examined gene transfer from bacteria to humans that would result in vertical inheritance. Bacterial DNA appears to integrate into the human somatic genome through an RNA intermediate, and such integrations are detected more frequently in tumors than normal samples and in RNA than DNA samples. Also, vertebrate viruses encode products that interfere with the RNA silencing machinery, suggesting that RNA silencing may indeed be important for antiviral responses in vertebrates. RNA silencing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…marinum , but intracellular levels of the sRNA were too low to repress target mRNA in cultured cells [ 39 ]. Moreover, a high-throughput bioinformatics approach predicted possible targets of bacterial sRNAs in the human transcriptome, and in vitro transfection of host cells with a selection of these putative sRNAs decreased target mRNA abundance [ 43 ]. However, the actual expression levels of the predicted sRNAs or their effect on a biological response, such as cytokine secretion, were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…marinum , but intracellular levels of the sRNA were too low to repress target mRNA in cultured cells [ 39 ]. Moreover, a high-throughput bioinformatics approach predicted possible targets of bacterial sRNAs in the human transcriptome, and in vitro transfection of host cells with a selection of these putative sRNAs decreased target mRNA abundance [ 43 ]. However, the actual expression levels of the predicted sRNAs or their effect on a biological response, such as cytokine secretion, were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies suggest that bacteria could also produce functional miRNA or miRNA-like snRNAs (12,13). In this study, we found that Wolbachia, as endosymbiotic bacteria, are able to encode snRNAs that act as effectors to modulate the expression of Wolbachia and mosquito host genes.…”
mentioning
confidence: 67%
“…This suggests that it may be a bacterial-derived miRNA released by infection of the macrophages. Bacterial-derived miRNAs have recently been extensively studied [ 39 , 40 ]. It is likely that these small RNA molecules may repress the ability of the host cell to resist bacterial invasion, as has been shown for viruses and fungi [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%